Problematyka pedagogiczna elementem doskonalenia wykładowców teologii w Polsce w latach 1918-1939 - Skoczylas, Kazimierz (Collectanea Theologica, 2019)
Pedagogical issues were present in senior seminaries in Poland in the interwar period. The interest in this subject was inspired by Jan Kanty Association of Theological Schools. The members of this association were lecturers of various theological subjects of higher seminaries and theological faculties in Poland. The Association discussed both pedagogical and didactic problems. The teaching contents of particular subjects, the teaching methods, textbooks as well as ways to familiarize students of theology with pedagogical issues were discussed by it.